CD10+ Cells and IgM in Pathogen Response in Lumpfish (Cyclopterus lumpus) Eye Tissues - Gendron, Robert L.; Paradis, Hélène; Ahmad, Raahyma; Kao, Kenneth; Boyce, Danny; Good, William V.; Kumar, Surendra; Vasquez, Ignacio; Cao, Trung; Hossain, Ahmed; Chakraborty, Setu; Valderrama, Katherinne; et al. (Frontiers in Immunology, 2020)
Lumpfish (Cyclopterus lumpus), a North Atlantic “cleaner“ fish, is utilized to biocontrol salmon louse (Lepeophtheirus salmonis) in Atlantic salmon (Salmo salar) farms. Lumpfish require excellent vision to scan for and eat louse on salmon skin. The lumpfish eye immune response to infectious diseases has not been explored. We examined the ocular response to a natural parasite infection in wild lumpfish and to an experimental bacterial infection in cultured lumpfish. Cysts associated with natural myxozoan infection in the ocular scleral cartilage of wild adult lumpfish harbored cells expressing cluster of differentiation 10 (CD10) and immunoglobulin M (IgM). Experimental Vibrio anguillarum infection, which led to exophthalmos and disorganization of the retinal tissues was associated with disruption of normal CD10 expression, CD10+ cellular infiltration and IgM expression. We further describe the lumpfish CD10 orthologue and characterize the lumpfish scleral skeleton in the context of myxozoan scleral cysts. We propose that lumpfish develop an intraocular response to pathogens, exemplified herein by myxozoan and V. anguillarum infection involving novel CD10+ cells and IgM+ cells to contain and mitigate damage to eye structures. This work is the first demonstration of CD10 and IgM expressing cells in a novel ocular immune system component in response to disease in a teleost.